Molecular Epidemiology of Human Metapneumovirus Infections in Children from San Luis Potosí-Mexico - Martínez-Marrero, Nadia; Muñoz-Escalante, Juan Carlos; Yerena-Rivera, Jan Michell; Jaime-Rocha, Luis Rubén; Leija-Martínez, José J.; González-Ortiz, Ana María; Noyola, Daniel E. (Viruses, 2025)
Lower respiratory infections are a leading cause of death in children under five years. Human metapneumovirus (HMPV) is an underestimated causal agent of these infections. In this study, the molecular epidemiology of HMPV associated with respiratory infections in Mexican children between August 2023 and August 2024 was determined. Sequences were also analyzed for predicted N- and O-linked glycosylation sites. Overall, 34 sequences from infants with respiratory infections were obtained; 32 were assigned to the A2b2 genotype, one to A2b1, and one to B2. All but one of the A2b2 sequences carried the 111-nucleotide duplication of the G gene; the remaining sequence carried the 180-nucleotide duplication. The samples assigned to the A2b1 and B2 genotypes did not have a duplication. The HMPV-A phylogeny did not show a clustering of Mexican sequences as a single monophyletic group. Four N-linked glycosylation sites were predicted in the HMPV-A sequences and three in the B sequence. The number of O-linked glycosylation sites predicted in HMPV-A ranged from 61 to 77 and were 61 in the HMPV-B sequence. This first description of HMPV genotypes and the diverse array of G protein N- and O-linked glycosylation patterns found in a Mexican pediatric population in the post-pandemic period contributes to the understanding of the global spread of HMPV.